2016
DOI: 10.2169/internalmedicine.55.6919
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related Disease Involving Multiple Organs with Elevated Serum Interleukin-6 Levels

Abstract: A 63-year-old woman presented to our hospital with elevated levels of serum IgG4, marked wall thickening of the gallbladder, hepatomegaly, and abdominal lymphadenopathy. She experienced a recurrent fever and leg edema. Her laboratory data demonstrated anemia, hypoalbuminemia, and elevated serum levels of interleukin-6 and C-reactive protein. The patient was eventually diagnosed with IgG4-related disease according to the comprehensive diagnostic criteria, although the patient exhibited common clinical manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Excessive expression of RANKL was also reported in lymphoma [12], adult T cell leukemia [13], and chronic lymphocytic leukemia [14]. In IgG4RD, there are a number of reports which described an elevation of serum IL-6 [15][16][17]. However, an abnormality of serum Ca concentration was not reported.…”
Section: Discussionmentioning
confidence: 98%
“…Excessive expression of RANKL was also reported in lymphoma [12], adult T cell leukemia [13], and chronic lymphocytic leukemia [14]. In IgG4RD, there are a number of reports which described an elevation of serum IL-6 [15][16][17]. However, an abnormality of serum Ca concentration was not reported.…”
Section: Discussionmentioning
confidence: 98%
“…Clinically, a favorable treatment response to PSL therapy may indicate a greater possibility of IgG4-RD than that of MCD. [39] Only few studies have reported IgG4-RD with elevated serum IL-6 levels [39][40][41], and the role of IL-6 in patients with IgG4-RD remains unclear. As IgG4 levels have not been reported for all previous cases of TAFRO syndrome, further studies are needed to discuss the association between TAFRO syndrome and elevated IgG4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of 10 patients with elevated serum IL-6 are shown in Table 3. Fig 1 shows CT images from a 63-year-old woman who complained of recurrent fever and exhibited elevated serum IL-6 (34 pg/mL) and was diagnosed with IgG4-RD [8]. Laboratory data at onset revealed anemia (hemoglobin, 7.8 g/dL), hypoalbuminemia (albumin, 1.5 g/dL), and elevated serum levels of IgG4 (1080 mg/dL) and CRP (5.05 mg/dL).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…IL-6, a principal mediator in inflammatory conditions, is reportedly a marker that is indicative of severity, progression, and outcome in several diseases [5]- [6]. Although MCD and IgG4-RD are thought to be distinct clinical entities, some patients with IgG4-RD exhibit elevated serum IL-6 [7]- [8], and in such patients it can be difficult to distinguish their condition from MCD.…”
Section: Introductionmentioning
confidence: 99%